Replication Data for: Implications of a changing climate on food security and smallholders livelihoods in Bogotá, Colombia - Eitzinger, Anton; Läderach, Peter R.D.; Bunn, Christian; Quiroga, Audberto; Benedikter, Andreas; Pantoja, Antonio; Gordon, Jason; Bruni, Michele (2013)
In our multidisciplinary methodology, we translated the exposure to CC into direct impact on crops and assessed sensitivity and adaptive capacity using the sustainable rural livelihoods framework